2013
DOI: 10.1021/cn400105d
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Fe(III)-Catalyzed Dopamine Oxidation by ATP and Its Relevance to Oxidative Stress in Parkinson’s Disease

Abstract: Parkinson's disease (PD) is characterized by the progressive degeneration of dopaminergic cells, which implicates a role of dopamine (DA) in the etiology of PD. A possible DA degradation pathway is the Fe(III)-catalyzed oxidation of DA by oxygen, which produces neuronal toxins as side products. We investigated how ATP, an abundant and ubiquitous molecule in cellular milieu, affects the catalytic oxidation reaction of dopamine. For the first time, a unique, highly stable DA−Fe(III)−ATP ternary complex was forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 50 publications
5
35
0
Order By: Relevance
“…[28,36]. Such a complex is capable of binding the oxidant to form a ternary complex, thus making the easy arrival of DA molecules to the surface of the modified electrode [37]. In this study, we suggest the following general mechanism for the oxidation of DA on the Au/Fe6 electrode:…”
Section: Electrochemical Behavior Of Da At Au/fe Electrodesmentioning
confidence: 89%
“…[28,36]. Such a complex is capable of binding the oxidant to form a ternary complex, thus making the easy arrival of DA molecules to the surface of the modified electrode [37]. In this study, we suggest the following general mechanism for the oxidation of DA on the Au/Fe6 electrode:…”
Section: Electrochemical Behavior Of Da At Au/fe Electrodesmentioning
confidence: 89%
“…It has previously been shown that the oxidation of DA can be catalyzed in the presence of iron (Chinta and Andersen ; Jiang et al . ) resulting in an abnormal accumulation of the intermediate oxidation product 6‐hydroxydopamine (Pezzella et al . ) and enhanced formation of neuromelanin, the end‐product of the oxidation of dopamine (Sulzer et al .…”
mentioning
confidence: 99%
“…In addition, a number of the previous studies have used extremely high iron concentrations (Jiang et al . ), low pH (García et al . ) or complexing buffer solutions (Napolitano et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations